Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik di Kelas 1 Sekolah Dasar - Fatmawati, Rini; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The purpose of this study was to improve the integrated thematic learning process using the scientific approach in grade 1 elementary school. The subjects of this study were researchers as teachers, and 27 grade students. In this study applying the type of PTK research. This study uses a qualitative and quantitative approach. The results showed an increase in: (a) the first cycle RPP obtained an average value of 81.9% (B) and cycle 2 to 97% (A), (b) assessment of aspects of the cycle teacher I obtained an average value of 80% (B) and cycle 2 to 96% (A), (c) assessment of aspects of cycle 1 students obtained an average value of 78% (B) and cycle 2 to 92%